The country where teachers are honorable Syrdarya region of the Republic of Uzbekistan - Orifjonova Nigora Rahimjon Kizi; Maftunakhon Nematova Alisher Kizi (Universitas Muhammadiyah Sidoarjo, 2020)
Paper investigates major points and status quo of the teachers in Uzbekistan. In this article attention for the teachers of Uzbekistan and works had been done in this sphere were examined. On this way, The country where teachers are honorable Syrdarya region of the republic of Uzbekistan